Evaluation and Analysis of M&A’s Impact on Firm Performance in Pharmaceutical Industry - Sheng, Qiyuan (2013)
At present, mergers and acquisitions play a very important role in firm’s business strategy. As a result, more and more companies attempt to engage in M&A activities for further development. In this dissertation, the aim is to evaluate and analyze the M&A’s impact on pharmaceutical companies’ performance. Firstly, some background of M&A would be introduced in the introduction chapter like its definition, historical developments and its types. Then in the literature review chapter, the motives for engaging in M&A, determinants of companies' performance following M&A and empirical studies of M&A are discussed and some M&A theories are presented as well. For the methodology and analysis parts, the accounting analysis and the event study are used in turn to prove the M&A theories mentioned in the literature review. Finally, the conclusion of this dissertation is reached.